2011
DOI: 10.3174/ajnr.a2828
|View full text |Cite
|
Sign up to set email alerts
|

Tuberothalamic Artery Infarctions following Coil Embolization of Ruptured Posterior Communicating Artery Aneurysms with Posterior Communicating Artery Sacrifice

Abstract: BACKGROUND AND PURPOSE:Ischemic complications after coil embolization of the PcomA aneurysms are not thoroughly understood, especially in cases in which the PcomA is sacrificed. Our purpose was to examine the preoperative angiographic features and pattern of postoperative cerebral infarctions exhibited by patients who underwent embolization of ruptured PcomA aneurysms with PcomA sacrifice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 22 publications
1
41
2
Order By: Relevance
“…1 However, ischemic complications following coil embolization of PcomA aneurysms are not fully understood, especially when the PcomA is sacrificed. 16 Although the Allcock test is considered useful for evaluating collateral blood flow, to predict postoperative ischemic complications of PcomA sacrifice, the ramifications of sacrificing the PcomA orifice in patients with PcomA aneurysms are still unknown. Endo et al 16 reported 7 cases of tuberothalamic artery territory infarction following coil embolization of 14 ruptured PcomA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, ischemic complications following coil embolization of PcomA aneurysms are not fully understood, especially when the PcomA is sacrificed. 16 Although the Allcock test is considered useful for evaluating collateral blood flow, to predict postoperative ischemic complications of PcomA sacrifice, the ramifications of sacrificing the PcomA orifice in patients with PcomA aneurysms are still unknown. Endo et al 16 reported 7 cases of tuberothalamic artery territory infarction following coil embolization of 14 ruptured PcomA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although the Allcock test is considered useful for evaluating collateral blood flow, to predict postoperative ischemic complications of PcomA sacrifice, the ramifications of sacrificing the PcomA orifice in patients with PcomA aneurysms are still unknown. Endo et al 16 reported 7 cases of tuberothalamic artery territory infarction following coil embolization of 14 ruptured PcomA aneurysms. PcomA sacrifice was regarded as unsafe, even with a preoperative Allcock test confirming retrograde filling of the PcomA by the posterior cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…Endo et al used coil embolization and PcoA occlusion to treat 14 patients with ruptured PcoA aneurysms,4 confirming retrograde filling of PcoA through P1 by the Allcock test before each procedure. Nevertheless, half of their patients developed postprocedural infarcts in territories of tuberothalamic arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Endo et al were the first to address PcoA compromise in PcoA aneurysms, finding that 50% of patients thus treated suffered infarction after coil embolization. They attributed the above outcomes to compromise in instances of PcoA dominance 4. Cho et al have nevertheless argued that compromise of hypoplastic PcoA variants, in conjunction with coil embolization of PcoA aneurysms, appears to be safe with no major consequences 3.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the PCoA is obliterated near the ICA, the reverse flow of the PCoA from the PCA will perfuse ATPAs, and the diameter of the P1 segment is important. 17) A super-selective balloon test occlusion of the PCoA is seemed to be considered. 18) In our case, the aneurysmal neck was small, very close to the P1-P2 segment, and more than 5 mm away from PMA; therefore, we planned a short-segment internal trapping as a third session.…”
Section: Case Presentationmentioning
confidence: 99%